Memprediksi Niat Beli Produk Fashion Melalui Aplikasi Marketplace Dengan Theory Planned Behaviour Dan Product Knowledge Sebagai Variabel Moderasi Dengan Analisa Partial Least Square (PLS) - Sulasih Sulasih; Suliyanto Suliyanto; Weni Novandari; Azizahtul Munawaroh (el-Jizya : Jurnal Ekonomi Islam, 2022)
The purpose of this study was to examine the behavior of UIN Saizu students using The Theory Planned Behaviour (TPB) related to the intention to buy fashion products using a marketplace application with product knowledge as the moderating variable. The number of samples is 100 UIN Saizu students with purposive sampling technique. Partial Least Square (PLS) was used to analyze the data in this study. The results of this study indicate that attitudes have a positive relationship and have a significant effect on the purchase intention of fashion products through marketplace applications. Likewise, Perceived Behavior Control and product knowledge have an effect and have a positive relationship on the purchase intention of UIN Saizu students on fashion products using marketplace applications. While subjective norm have no significant effect on the intention to buy fashion products through the marketplace. Likewise, attitudes, subjective norm and perceived behaviour control moderating knowledge have no significant effect on purchase intention of fashion products through marketplace applications. Based on the conclusions above, it can be suggested in the following research to use knowledge as a mediating variable and add the factors used as variables that have been shown to influence behavioral intentions, especially in purchasing fashion products through marketplace applications.